Swedish Labor Market Policy. Fact Sheets on Sweden - Swedish Inst., Stockholm; Swedish Inst., Stockholm ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
This paper contains an overview of labor market policy in Sweden. It refers to job placement services and other more or less selective measures to improve opportunities for people to obtain and retain a job. The paper first examines the objectives of labor market policies since the 1950s, then it highlights such labor market trends as the increase in unemployment from the 1960s to the 1980s, slow economic growth, and the increasing number of unemployed young people. The next section explains the structure of the Labor Market Administration. It is followed by a discussion of types of labor market policy measures, such as matching measures, measures to influence labor supply, and measures to influece labor demand. The final two sections examine regional development aid and cash benefits to the unemployed. (KC)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Employment Patterns; Employment Problems; Foreign Countries; Labor Conditions; Labor Economics; Labor Force; Labor Market; Labor Supply; Public Policy; Quality of Working Life; Unemployment; Sweden; Reports, Descriptive